2009
DOI: 10.1161/strokeaha.108.520262
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone, a Free Radical Scavenger, Inhibits MMP-9–Related Brain Hemorrhage in Rats Treated With Tissue Plasminogen Activator

Abstract: Background and Purpose-Intracerebral hemorrhage, induced by recombinant tissue plasminogen activator (rtPA) in ischemic stroke, is attributable to the increased activity of matrix metalloproteinase-9 (MMP-9). Patients with acute infarct benefit from the neuroprotective drug edaravone, a free radical scavenger. We examined the mechanisms by which edaravone may help to suppress rtPA-induced brain hemorrhage. Methods-Male Wistar rats weighing 250 to 280 g were subjected to 3-hour transient middle cerebral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 27 publications
(42 reference statements)
4
86
1
1
Order By: Relevance
“…Further studies found that this agent performs its beneficial effects via MMP-9 inhibition as well [166]. Since 2001 in Japan, edaravone is an approved treatment of ischemic stroke when administered within the first 24 hours of onset.…”
Section: Edaravonementioning
confidence: 99%
“…Further studies found that this agent performs its beneficial effects via MMP-9 inhibition as well [166]. Since 2001 in Japan, edaravone is an approved treatment of ischemic stroke when administered within the first 24 hours of onset.…”
Section: Edaravonementioning
confidence: 99%
“…To take advantage of the beneficial role of MMP-9 in the sub-acute phase of stroke as well as to avoid its deleterious effects including hemorrhage and cell death [10,34] , we used an HRE-HIF system to control the expression of MMP-9 in the sub-acute phase of stroke ( Fig. 2A).…”
Section: Hre-controlled Mmp-9 Expression Level In the Ischemic Mouse mentioning
confidence: 99%
“…Certain research groups have reported that the administration of edaravone increased the survival rate, and inhibited alteplase-induced hemorrhagic transformation, blood-brain barrier damage and oxidative stress in the ischemic brains of rats, and hypothesized that edaravone may reduce the activity of matrix metalloproteinase-9 (MMP-9) (43)(44)(45)(46). In their study, Kano et al (47) reported that edaravone attenuated the extravasation of alteplase through the cerebral vessels in a rat model of AIS.…”
Section: Combination Therapy Using Alteplase and Edaravonementioning
confidence: 99%